2018
DOI: 10.1521/bumc.2018.82.3.202
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of mentalizing between attachment and eating disorders

Abstract: The objective of the study was to investigate whether mindfulness mediated the relationship between attachment and eating disorders in a sample of 323 female university students and 38 anorexic inpatients using structural equation modeling. All insecure attachment subscales were positively related to eating disorder symptoms and negatively to mindfulness. Furthermore, mindfulness scores were negatively associated with eating disorder symptoms. Mediation analyses showed that the relationship between all the ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Reduced mindfulness capacity (i.e., inability to be fully aware of current experience or present reality) [106] was also identified as one of the mediating mechanisms [51,63]. This result is not surprising as the associations between insecure attachment and mindfulness [106108] and between mindfulness and eating pathology [109,110] have been previously established.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Reduced mindfulness capacity (i.e., inability to be fully aware of current experience or present reality) [106] was also identified as one of the mediating mechanisms [51,63]. This result is not surprising as the associations between insecure attachment and mindfulness [106108] and between mindfulness and eating pathology [109,110] have been previously established.…”
Section: Discussionmentioning
confidence: 95%
“…Eleven studies used clinical samples, including Pepping’s et al [51] work referred to patients and three studies that combined samples of patients with EDs and healthy participants when performing the mediating analyses [59,61,63]. Three studies compared clinical and healthy samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to predicting the development of ED symptoms [42,51], degree of mentalization has been associated with the formation of physical complaints and somatization [48,52,53] that have been identified as potential core predictors of obesity [54][55][56]. Numerous studies have confirmed the existence of insecure attachment and impaired RF in people with EDs [50,[57][58]. The prevalence of insecure attachment among obese patients is also reported to be higher than the general population [59][60].…”
Section: Introductionmentioning
confidence: 99%